Improved Outcomes With an Enhanced Recovery Approach to Cesarean Delivery. Issue 4 (October 2020) - Mullman, Luciana; Hilden, Patrick; Goral, Jan; Gwacham, Nnamdi; Tauro, Caitlin; Spinola, Kristen; Rosales, Kim; Collier, Sheila; Holmes, Lynice; Maccione, Janice; Pitera, Richard; Miller, Richard; et al.
Abstract : OBJECTIVE: To examine the results of a quality-improvement study that implemented an enhanced recovery after surgery (ERAS) program for cesarean delivery. METHODS: A pre–post design was used to assess changes in opioid use, length of stay, and costs among all patients undergoing cesarean delivery before and after implementation of an evidence-based ERAS pathway for the preoperative, intraoperative, and postoperative management of patients beginning December 2018. RESULTS: A total of 3, 679 cesarean deliveries (scheduled and emergent) were included from January 1, 2018, through August 31, 2019, of which 2, 171 occurred before implementation on December 17, 2018, and 1, 508 occurred postimplementation. Eighty-four percent of patients received opioids as inpatients after cesarean delivery during the preimplementation period, as compared with 24% in the postimplementation period (odds ratio [OR] 16.8, 95% CI 14.3–19.9). Among patients who required any opioids, the total morphine milligram equivalents also significantly decreased (median 56.5 vs 15.0, mean relative change 0.32, 95% CI 0.28–0.35). Compared with the preimplementation period, those in the postimplementation period had a shorter postcesarean length of stay (3.2 vs 2.7 days, mean relative change 0.82, 95% CI 0.80–0.83, median 3 days in both periods), lower median direct costs by 349 (mean relative change 0.93, 95% CI 0.91–0.95), and no change in the 30-day readmission rate (1.4% vs 1.7%, OR 0.83, 95% CI 0.49–1.41). CONCLUSION: An ERAS approach for the cesarean delivery population is associated with improved outcomes including decreases in opioid use, length of stay, and costs. Abstract : Implementing an enhanced recovery after surgery program for cesarean delivery is associated with reduced length of stay, cost of care, and opioid analgesia use.